Income And Subjective Well-Being In Malaysia - Boo, Mei Chin (2018)
Can money buy happiness? The income-happiness puzzle (Easterlin Paradox) points out that individuals with higher incomes are happier than people with lower incomes yet raising everyone’s income does not compensate with overall higher levels of happiness. This thesis aims to examine income and subjective well-being in Malaysia. The research focuses on two measures of subjective well-being – happiness and life satisfaction. Based on the wave 5 (2005-2009) and wave 6 (2010-2014) data obtained from the World Values Survey, this study addresses the issue of subjective well-being inequalities from different income groups. The survey was carried out in year 2006 for wave 5 and year 2011 for wave 6. People were happier and more satisfied in year 2011 compared to year 2006. However, over the same period, happiness and life satisfaction inequalities were found to be higher among the low-income group compared with the higher income groups. This study also examines the influence of absolute income, relative income and expected income on happiness and life satisfaction based on wave 6. Using the ordered logit regression analysis, it is found that higher absolute income contributes to greater happiness and satisfaction levels among Malaysians. In terms of the role of relative income on happiness, ‘tunnel effect’ is observed in particular among those in the low-income group. When compared with others who earn relatively higher income, Malaysians are less satisfied with life but the effect is found to be reversed in their happiness levels. Higher expected income seems to generate greater satisfaction among Malaysians. Other factors such as health, employment, religiosity, trust and democracy do influence Malaysian happiness and life satisfaction.